Comparison of William flexion exercise with combined stimulation of brain and back muscles in relieving non specific chronic low back pain - Abdulkareem Muhammad Umar
This study compared the effect of William flexion exercise and combined stimulation of two different regions of the brain and back muscles in the treatment of nonspecific chronic low back pain (CLBP). A total of 48 patients were recruited and assigned into four groups. The control group received infrared therapy (IRT) and soft tissue massage therapy (STM), while those in the other groups received combined dorsolateral prefrontal cortex (DLPFC) and back muscle stimulations plus IRT and STM, combined primary motor cortex (PMC) and back muscle stimulations plus IRT and STM, and William flexion exercise plus IRT and STM respectively. The primary outcome measure (pain intensity and disability level) was assessed using visual analoque scale and modified Oswestry low back pain disability questionnaire respectively, while bothersome questionnaire was used to assess the secondary outcome. The outcome of the study revealed a statistically significant median difference of pain intensity in all the interventions, including combined PMC and back muscle stimulation plus IRT and STM (P=0.002, Z=-3.16), combined DLPFC and Back muscle stimulation plus IRT and STM (P=0.007, Z=-2.71), William flexion exercise plus IRT and STM (P=0.005, Z=-2.83), and control group (P=0.005, Z=-2.83) respectively, while only those that received combined DLPFC and back muscle stimulation plus IRT and STM, and the control group have statistically significant median difference of disability at (P=0.046, Z=-2.02) and (P=0.025, Z=-2.24) respectively. However, there was no statistical significant median difference of the test variables between all the interventions. It was concluded that there was no significant difference between William flexion exercise and combined brain and back muscles stimulation in relieving nonspecific CLBP. Nevertheless, the result cannot cannot be generalized because of the small sample size used in the study.